A-180 Clinical Outcome Following Concussion Among Children and Adolescents with a History of Prior Concussion: A Systematic Review. (17th August 2022) - Cook, Nathan E; Gaudet, Charles E; Van Patten, Ryan; Kissinger-Knox, Alicia; Iverson, Grant L
Abstract: Purpose: This systematic review examined the association between prior concussion history and clinical outcomes following concussion among children and adolescents. Data Selection: This review was registered with PROSPERO database for systematic reviews (protocol ID: CRD42016041479 & CRD42019128300) and adhered to PRISMA guidelines. Three searches of nine online databases were conducted: (a) database inception to June of 2016; (b) January 1, 2016 to February 1, 2019; and (c) February 1, 2019 to May 15, 2021. We screened 5, 118 abstracts and 51 studies were reviewed. We utilized a likelihood heuristic to assess evidence for an association between concussion history and clinical outcomes. Risk of bias was assessed using the Newcastle-Ottawa scale and level of evidence was appraised using the Oxford Classification for Evidence-Based Medicine. Data Synthesis: Concussion recovery or outcome was reported for 26, 643 youth. A median of 36% had a prior history of concussion. Across all studies and outcomes, the majority (k=37, 72.5%) did not find a statistically significant association between lifetime history of concussion and outcome from a subsequent concussion. Important methodological limitations in the literature were identified (e.g., many studies were underpowered and/or coded prior concussion history as a binary variable as opposed to the number of prior concussions). Conclusions: Available studies do not provide compelling evidence that children and adolescents with a history of concussions are at increased risk for worse clinical outcome following a subsequent concussion. Clinicians are cautioned against routinely treating children and adolescents with one or more prior injuries more conservatively. Doing so, in some cases, might be counterproductive.